A conceptual model of tacit knowledge transfer in steganography - Hasnita Abdul Talib, Noor; Ahmad, Mazida; Din, Roshidi (International Journal of Engineering and Technology, 2018)
Steganography is a technique that involves a secret hidden message concealed inside the media cover using formats such as text, images, video or audio. Secret messages sent from the sender to the receiver are considered as knowledge being transferred from the expert to the novice. However, previous studies related to the knowledge transfer from experts to novices in the field of computer security, particularly in the field of steganography, are limited. Therefore, this study aims to investigate the knowledge transfer process occurring in steganography by using an information management transfer model. The methodology consists of theory development, model validation, instrument development, survey and model verification. This paper proposes a novel Stego-based SECI Model that demonstrates how the knowledge transfer process occurs in steganography.Â Â